Thermodynamic properties of spin ladders with cyclic exchange - Schmidt, Kai Phillip; et al. (Physical Review B, 2003)
By high-temperature series expansion and exact complete diagonalization the magnetic susceptibility chi(T) and the specific heat C(T) of a two-leg S=1/2 ladder with cyclic (four-spin) exchange are computed. Both methods yield convincing results for not too small temperatures. We find that a small amount of cyclic exchange influences the thermodynamic properties significantly. Our results can serve as reliable basis for an efficient analysis of experimental data.